Laser-induced layers peeling of sputtering coatings at 1064 nm wavelength - Kesheng Guo (Nature Portfolio, 2021)
Abstract Large-scale layers peeling after the laser irradiation of dual ion beam sputtering coatings is discovered and a model is established to explain it. The laser damage morphologies relate to the laser fluence, showing thermomechanical coupling failure at low energy and coating layers separation at high energy. High-pressure gradients appear in the interaction between laser and coatings, resulting in large-scale layer separation. A two-step laser damage model including defect-induced damage process and ionized air wave damage process is proposed to explain the two phenomena at different energy. At relatively high energies (higher than 20 J/cm2), ionization of the air can be initiated, leading to a peeling off effect. The peeling effect is related to the thermomechanical properties of the coating materials.